Food Estate Papua Sebagai Jawaban dari Solusi Berkelanjutan terhadap Ketahanan Pangan Indonesia - Salma Sary Heryani (Spektrum, 2026)
The realisation of the food estate is still causing polemics regarding its adverse impacts. The food estate is believed to be a project that will succeed in maintaining national resilience, but it has a negative impact on local communities. Papua was targeted after other areas were believed to have failed, but the government seems confident that the contribution of food estate in Papua can overcome Indonesia's food security problems. This article looks at the extent to which the Food Estate in Papua can contribute to the country being able to fulfil domestic needs from its own production of staple food commodities. The findings indicate that the Food Estate in Papua is not a solution to food‑security challenges. rather, it is an instrument that can make a genuine contribution only if its governance is fundamentally redesigned. The Food Estate in Papua is not the sole alternative for resolving food‑security issues; it is an instrument that can contribute meaningfully only when its governance is re‑engineered. A holistic and sustainable approach is required. Without such an approach, the Food Estate in Papua risks repeating the failures of previous projects, in which large‑scale schemes and short‑term production targets compromised social and environmental stability and the rights of local communities.